Effect of natural catastrophes on stock prices : evidence from Indonesia, Malaysia and Thailand - Kho, Geok Hui (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study examines the effect of natural catastrophes on the stock returns of the firms listed in Indonesia, Malaysia, and Thailand stock exchange and operating in automobile and parts, construction and material, food producers, technology hardware and equipment, and travel"and leisure industry. This study only examines the effect of natural catastrophes on the stock returns in the post-event. An event study methodology has been employ in this study by adopted CAPM to estimate the AR and CAAR for the event period. The result shows that, the effect of natural catastrophes on stock prices is negative to the industries in Indonesia and Thailand. Only industries in Malaysia had the positive to the natural catastrophes on stock prices. Overall, the finding indicates that natural catastrophes have effect to the stock prices. In addition, the results seemed to indicate that the market in Malaysia is more or less efficient except for few days and in Indonesia and Thailand market are somewhat inefficient.